Turning the tide–why cities can be both drivers of climate change and biodiversity loss, and leaders in tackling them - Haase, Dagmar (Frontiers in Environmental Science, 2025)
Preface. This perspective uses the key features of the “city” system to prevent the triad of climate, biodiversity and socio-economic inequality crises from worsening. In other words, global change key drivers know how to make things better. The perspective discusses the idea of cities as both a cause and a solution to planetary challenges, such as climate change, biodiversity loss and socio-environmental as well as health inequalities. Unlike many other articles on urbanisation as a driver of environmental problems, this article does not focus exclusively on this role. Instead, it links urbanisation to its tremendous potential to both cause and solve these environmental problems, drawing on the enormous innovative and communicative talent inherent in cities and urban societies. It offers a fresh, serious yet optimistic look at the role of cities in the global race to prevent critical tipping points for a broad urban-focused audience.